Developing scenarios in the context of the Paris Agreement and application in the integrated assessment model IMAGE: A framework for bridging the policy-modelling divide. Issue 135 (September 2022) - Roelfsema, Mark; van Soest, Heleen L.; den Elzen, Michel; de Coninck, Heleen; Kuramochi, Takeshi; Harmsen, Mathijs; Dafnomilis, Ioannis; Höhne, Niklas; van Vuuren, Detlef P.
Abstract: The framework presented in this study aims to provide insights into how climate policy is represented in integrated assessment models, responding to the call to link model scenarios with concepts used in public policy literature and related fields. As such, it contributes to increased transparency leading to better understanding across disciplines and communication about the relevance of model outcomes with policymakers. The framework categorises climate policy into policy aims and policy implementation at different stages of the policy cycle, and can be used to demarcate different climate policy scenarios incorporating and linking the international and national level. This approach provides clarity on critical modelling assumptions concerning the workings of policy to scenario users (including policymakers), such as policy stringency and status. We discuss the framework in relation to scenarios exploring pathways meeting the long-term Paris goal to hold temperature well below 2 °C or 1.5 °C, Nationally Determined Contributions submitted to the Paris Agreement, and current implemented policies. Specifically, the application of the framework and model implementation of the scenarios is illustrated with implementation in the IMAGE model. To project the expected policy impact on greenhouse gas emissions, the policy goals and policy instrument targets are translated into model targets. This is implemented in the model by either changing parameters for available policy instruments, such as carbon price or subsidies, or adjusting model parameters such as efficiency and costs to meet targets. Highlights: We developed a climate policy framework that integrates models and policy design. The framework helps modellers, scholars and policymakers speak the same language. This framework can be used to make policy representation in models more transparent. Models represent policy instruments by replicating the impact on emissions.